Uncovering the integral spectral characteristics of the planetary nebula IC 4642 - Mahmoud Mohery; Alaa Ali; Kholoud Ahmed Hamam; Aya Atef Khames; Abdullah Saad Alsubaie (Scientific Reports)
Abstract We report the first comprehensive spectroscopic analysis of the Galactic planetary nebula (PN; plural: PNe) IC 4642, using low-dispersion integral field unit (IFU) observations. The objective of this study is to derive detailed physical conditions, chemical compositions, ionization structures, and morphological characteristics of the PN. The physical and chemical assessments indicate that the PN is optically thin and falls into a high excitation class (EC = 11.0). Furthermore, the chemical analysis demonstrates that IC 4642 is deficient in helium and nitrogen, exhibiting a nitrogen-to-oxygen (N/O) ratio of $$\sim 0.1$$ , which classifies it as a non-type I PN. This classification aligns with the derived radial peculiar velocity of $$123 ± 19$$ km $$\hbox {s}^{-1}$$ and a distance of $$\sim 670$$ pc from the mid-Galactic plane, suggesting that this PN is the remnant of an old, low-mass star belonging to the Galactic thick-disk population. To explore the morphology and ionization structure of IC 4642, we provided a set of emission-line maps that represent various elements and ionization states. The analysis of these maps reveals an overall elliptical morphology with two longitudinal inner structures, indicative of a probable bipolar configuration accompanied by an equatorial torus. Recent observations from the Gaia space mission have identified the central star (CS) of the PN as a variable star. In alignment with the explanations presented in the literature concerning the morphology of the PN, one plausible interpretation for the observed variability of the CS is that it may be a member of a binary system accompanied by a sub-stellar companion in a common envelope phase.